2012
DOI: 10.4049/jimmunol.1101746
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mast Cells and Basophils in IgE Responses and in Allergic Airway Hyperresponsiveness

Abstract: We established a diphtheria toxin (DT)-based conditional deletion system using Il4 enhancer elements previously shown to be specific for IL-4 production in mast cells (MCs) or basophils (Mas-TRECK and Bas-TRECK mice). DT treatment of Bas-TRECK mice resulted in specific deletion of basophils, whereas both MCs and basophils were deleted in Mas-TRECK mice. DT-treated Mas-TRECK mice had impaired passive cutaneous anaphylaxis, IgE-mediated passive systemic anaphylaxis, and IgE-mediated chronic allergic inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
153
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(161 citation statements)
references
References 49 publications
(50 reference statements)
8
153
0
Order By: Relevance
“…We used genetic approaches to investigate the relative contributions of MCs and basophils in primary and secondary infections with S. venezuelensis. MC-deficient WBB6F 1 -Kit W/W-v mice exhibited delayed expulsion of S. venezuelensis in primary infections (6,7,11), but such mice have other abnormalities related to their c-kit mutations that may influence the response to this parasite by mechanisms unrelated to their MC deficiency (17,(32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used genetic approaches to investigate the relative contributions of MCs and basophils in primary and secondary infections with S. venezuelensis. MC-deficient WBB6F 1 -Kit W/W-v mice exhibited delayed expulsion of S. venezuelensis in primary infections (6,7,11), but such mice have other abnormalities related to their c-kit mutations that may influence the response to this parasite by mechanisms unrelated to their MC deficiency (17,(32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…1B). Another genetically engineered MC-deficient mouse (with normal c-kit), the MasTRECK (Tg/ϩ) mouse (32), exhibited a 7-day delay in cessation of egg excretion compared to diphtheria toxin (DT)-treated littermate wildtype control (ϩ/ϩ) or phosphate-buffered saline (PBS)-treated MasTRECK mice ( Fig. 1C; also see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The probable reason for this difference is that passive sensitization with monoclonal IgE is less efficient, due to the instability of IgE, compared with a polyclonal IgE antibody response. Recently, Sawaguchi et al showed that in a passive systemic anaphylaxis model, mast cell but not basophil depletion inhibited anaphylaxis [38]. In addition, Ohnmacht et al [40] demonstrated for the Mcpt8Cre-basophil-deficient mouse model that in active systemic anaphylaxis no difference between controls and the basophil-lacking mice exist.…”
Section: Discussionmentioning
confidence: 99%
“…If we obtain concordant results in both types of MC-deficient mice, we then proceed to engraftment experiments to ascertain the role of MCs and assess the potential roles of certain MC-derived products. Finally, it should be noted that several strains allowing inducible depletion of MCs or Cre recombinase-mediated deletion of "floxed" genes in MCs have also been recently described 25,49,61 . These strains have been reviewed in detail elsewhere 9,10,13 and represent promising alternative -or complementary -approaches to study MC functions in vivo.…”
Section: Discussionmentioning
confidence: 99%